Representation of the Hedonism of the Main Character in Kevin Kwan's Chinese Novel Rich Girlfriend - Titiani Intan Firdaus (Syntax Idea)
This study aims to describe the picture of hedonism carried out by the main character in the Chinese novel Rich Girlfriend by Kevin Kwan The method used is descriptive qualitative with data collection techniques using the listen and record technique method. Data analysis techniques include six stages, namely, problem identification, problem formulation, preparation of conceptual or theoretical frameworks, formulation of hypotheses, research methods which include methods of data collection and analysis, and drawing conclusions of research results. The results of this study show that of the five types of lifestyles that affect cultural development in society, namely entertainment, food, fashion, music, and famous places, only three were found, namely entertainment, fashion, and famous places. The hedonic lifestyle in this novel is dominated by famous places, many of the places mentioned are the most expensive and luxurious places in the world.